The Amplifying Effect of Conflicts on Case Fatality Rate of COVID-19: Evidence From 120 Countries - Zhai, Yonghui; Jiang, Dayang; Gozgor, Giray; Cho, Eunho (Frontiers in Public Health, 2021)
Using the COVID-19 database of Johns Hopkins University, this study examines the determinants of the case fatality rate of COVID-19. We consider various potential determinants of the mortality risk of COVID-19 in 120 countries. The Ordinary Least Squares (OLS) and the Kernel-based Regularized Least Squares (KRLS) estimations show that internal and external conflicts are positively related to the case fatality rates. This evidence is robust to the exclusion of countries across different regions. Thus, the evidence indicates that conflict may explain significant differences in the case fatality rate of COVID-19 across countries.